Comparison Of Murotal And Music Therapy Against People With Hypertension In Elderly At Parlors Tresna Wherdha Mulya Dharma Pontianak - Haryanto Haryanto; Tutur Kardiatun; Andi Maulana (Jurnal Keperawatan dan Kesehatan, 2014)
Background: The Elderly have high risk in hypertension, murrotal and music therapy have benefits to lower blood pressure in people with hypertension. Objective: This study aims to identified murrotal and music therapy in comparison to patients with hypertension in elderly at tresna wherdha mulyadharma Pontianak. Methods: This research used experimental pure design (Pure Experiment), a sample of 45 elderly people use the Systematic sampling and part into three groups, murrotal (intervention) therapy, music therapy (control +), non intervention (control-), the analysis used is one way anova test on systole with post hock bonferroni and krusskal wallis test and on diastole with post hock mann whitney test. Results: On the first day, there is no comparison of systole pressure using murrotal and music therapy against sufferers of hypertension on elderly p value = (0.177) > 0.05. Whereas, in the second and third day has comparison of systole pressure use murrotal therapy and music against sufferers of hypertension in the elderly (0.006, 0.001) < 0.05. On the first, second and thirdday has comparison of diastole blood pressure using music and murrotal therapy of patients with hypertension in elderly p value = (0000, 0.001, 0.001) < 0.05. Conclusion: Murrotal therapy and Music effectively was lower blood pressure in people with hypertension, but more effective murotal therapy in lowers blood pressure rather than music therapy.